Base plate: Interface between steel and concrete (Research, Society and Development, 2019)
A piece of great importance in the metallic structure, the base plates, pass unnoticed by the public eye in general, it justifies the nonobservance even by the place where they work that after finishing the structure they become invisible pieces, with a paper the whole of the structure, whereby they pass all the load directed to the foundation and are not always and given the due attention, which, once settled, become almost irreplaceable  and can in a short time cause serious structural problems causing damages and damaging the image of metal construction has enormous potential for growth in Brazil. In this study, we will present test results that demonstrate how these pieces work and how, if poorly designed, they potentiate future pathologies. These tests will be comparative only for visualization of the problematic involving these elements.